Reflections to decolonize the latinamerican academic culture in Communication - Castro-Lara, Eloína (2016)
It would be unlikely to decolonize the communicational practices and lore anchored in the coloniality of power of the current knowledge politics and in the traditional authorize voices that indicate what, who, how, when and where to problematize Communication. This paper suggests the necessity of its “liberation” –held by the epistemological state of the field- based on some other ways of being-knowing in the edge of a decolonized knowledge, gestated not only by the mere de-westernization in the intellectual production, intervention and understanding of communication processes, but also through epistemic disobedience.